2009
DOI: 10.1371/journal.ppat.1000380
|View full text |Cite
|
Sign up to set email alerts
|

Haemonchus contortus Acetylcholine Receptors of the DEG-3 Subfamily and Their Role in Sensitivity to Monepantel

Abstract: Gastro-intestinal nematodes in ruminants, especially Haemonchus contortus, are a global threat to sheep and cattle farming. The emergence of drug resistance, and even multi-drug resistance to the currently available classes of broad spectrum anthelmintics, further stresses the need for new drugs active against gastro-intestinal nematodes. A novel chemical class of synthetic anthelmintics, the Amino-Acetonitrile Derivatives (AADs), was recently discovered and the drug candidate AAD-1566 (monepantel) was chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
105
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 47 publications
6
105
1
1
Order By: Relevance
“…RNA extraction, cDNA synthesis, and PCR amplification of mptl-1 were performed, as described previously in Rufener et al (2009). In brief, total RNA was extracted from a pool of adult nematodes, and 1 mg total RNA (DNase-treated) was reverse-transcribed to cDNA using a (dT)30 primer and SuperScript III Reverse Transcriptase (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA extraction, cDNA synthesis, and PCR amplification of mptl-1 were performed, as described previously in Rufener et al (2009). In brief, total RNA was extracted from a pool of adult nematodes, and 1 mg total RNA (DNase-treated) was reverse-transcribed to cDNA using a (dT)30 primer and SuperScript III Reverse Transcriptase (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The same procedure was used to obtain the mptl-1 sequence with a 127-bp deletion (removing the entire exon 15) from the H. contortus AAD-mutant nematodes. The Hco-ric-3 gene was amplified using the same primers as described in Rufener et al (2009). The selected inserts were subcloned into a pT7-TS transcription vector (that introduces Xenopus laevis b-globin untranslated DNA to the 59 and 39 end of the gene) via the restriction sites inserted in the primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A molecular genetic approach with the nematode Caenorhabditis elegans indicated that the AADs, too, acted via ligand-gated ion channels: in mutagenized worms subjected to sublethal doses of AAD, loss of sensitivity was mapped to a gene encoding a putative nicotinic acetylcholine receptor (nAChR) ␣ subunit, ACR-23 (Kaminsky et al, 2008a). Related genes were found to be involved in H. contortus, in which loss-of-sensitivity mutants carried a panel of nonsense mutations and mis-splicing mutations in the two nAChR genes Hco-des-2 and Hco-mptl-1 (Rufener et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 Similarly, mutations in the homolog mptl-1 were isolated from AAD-resistant H. contortus species. 13 Since monepantel does not kill C. elegans, one can easily imagine that under constant selective pressure, the more tolerant individuals are given the possibility to escape and to reproduce. With parasitic nematodes such as H. contortus, paralysis would result in its elimination through the feces.…”
mentioning
confidence: 99%